The Implementation of The Concept of Maslahat (Benefits) in Determining The Minimum Age of Marriage in Islamic Family Law in Indonesia and Jordan - Bunyamin, Mahmudin (Universitas Islam Negeri Raden Intan Lampung, 2021)
This study examines the development of Islamic Family Law (al-Ahwāl al-Syakhshiyah) in modern Islamic countries, especially in Indonesia and Jordan. The aim is to gain a deep understanding of the phenomenon which has become a new strategic way to accommodate the idea of Islamic law reform into a more actual form. This research is descriptive-qualitative literature research. Qualitative research is a research procedure that produces descriptive data in the form of written speech, and observed behavior of research subjects. This study finds the fact that the concept of maslahat applied in marriage law in Indonesia and Jordan aims to achieve the general benefit, reject harm, preserve laws or regulations that have been in effect and are considered good, and develop them following Islamic law and the values of local wisdom that become characteristics of each country. Viewed from the other side, the phenomenon of family law reform that is developing in several Muslim countries today can be seen as the beginning of the process of transitioning fiqh law to positive law which is manifested in the form of national legislation.